Assessing the impact of the journey plus curriculum on sexual and reproductive health and rights and behavioural change among Ugandan youth - Kagurusi, Patrick; Nankanja, Maureen; Muyonga, Michael; Ayanga, Irene; Tigaiza, Arnold; Okimait, David; Nabacwa, Mary Ssonko (African journal of reproductive health, 2025)
The Journeys Plus curriculum was introduced by the Government of Uganda in 2020 to impart knowledge and empower youth to practice positive behaviours. It also focuses on fostering supportive environments for youths in homes, communities, health facilities, and schools. AMREF Uganda implemented the curriculum in the districts of Budaka, Mbale, Kween, Namayingo and Kalangala, Bukwo, Mayunge, Bugiri and Iganga. This paper explores the outcomes and effectiveness of the intervention and examines its impact on learning, behavioural change, and youth empowerment, using a phenomenological study design among 360 purposively selected young people (9 -14 years) and 80 adults. Aided by Atlas ti software, deductive analysis was applied to the study findings. The findings suggest that the Journeys Plus curriculum has proven effective in promoting behavior change, enhancing knowledge of sexual and reproductive health and rights, practical vocational skills, empowering young people against gender-based violence, and fostering meaningful peer relationships.
Keywords: Journey’s Plus Curriculum; Sexual and Reproductive Health and Rights